Utilization and farmers’ knowledge on pigeonpea diversity in Benin, West Africa - Ayenan, Mathieu Anatole Tele (J Ethnobiol Ethnomed, 2017)
BACKGROUND: Understanding factors driving farmers’ uses of crop genetic resources is a key component not only to design appropriate conservation strategies but also to promote sustainable production. However, in Benin, limited information is available on farmers’ knowledge related to pigeonpea uses and conservation. This study aimed at i) identifying and investigating the different uses of pigeonpea in relation with socio-cultural factors, namely age, gender, ethnic group and respondents’ residence, ii) assessing pigeonpea varieties richness at household level and iii) evaluating the extent and distribution of pigeonpea varieties. METHODS: Three hundred and two farmers were surveyed using structured questionnaire. Direct observation, field visit and focus group discussion were carried out. Association between number of varieties maintained at household level and socio-cultural variables was tested. Mann-Whitney test was used to assess whether the number of varieties held by households headed by men and women were different. Distribution and extent of diversity was assessed through four cells analysis. RESULTS: Farmers in Benin mainly grow pigeonpea for its grains for home consumption. Pigeonpea’s stem and leaves are used for medicinal purposes to treat malaria, dizziness, measles, and eye infection. The ethnic group and the locality of residence of farmers influenced on the use of pigeonpea for medicinal purposes (P < 0.01). There was no significant association (P > 0.05) between the number of varieties held by household and the age of the respondent, number of years of experience in pigeonpea cultivation, the size of household, number of family members engaged in agricultural activities and gender. Farmers used criteria including seed colors, seed size, plant height, maturity groups and cooking time to classify their varieties. Varieties with white seed coat color were the most grown while varieties with black, red or mottled seed coat color are being abandoned and deserve to be conserved. CONCLUSION: Knowledge on medicinal uses of pigeonpea is vertically transmitted within community and pigeonpea varieties maintenance at household level does not depend on socio-cultural factors. This study will contribute to raise awareness on the various utilization of pigeonpea. In addition, it provides the basis for designing conservation strategies of pigeonpea genetic resources.